Development of Persuasive Communication–Based Digital Technology for the Early Detection of Students’ Mental Health - Siti Nur'aeni; Myrna Anissaniwaty; Zamzam Ginanjar; Raihan Abdul Jabar; Sindi Dewanti Maulida (UPT Publikasi Ilmiah UNISBA, 2026)
Behavioral and mental health issues among students have become an urgent concern in education, particularly in the post-pandemic era and amid increased exposure to digital technology. Early detection efforts continue to face challenges such as limited resources, stigma, and lack of interactive, communicative digital media. This study aims to develop a persuasive communication–based digital technology model within the PROTEKSI Fammi Program to optimize the early detection of students’ behavioral and mental health problems. The study adopts a mixed-methods approach using an explanatory sequential design. Qualitative data were collected through in-depth interviews and focus group discussions with teachers, parents, counselors, and students to identify communication needs and barriers. Quantitative data were obtained through surveys measuring changes in users’ knowledge, attitudes, and behavioral intentions following use of the PROTEKSI digital prototype. The findings show that the proposed model increases user engagement, enhances awareness of early mental health indicators, and strengthens the involvement of teachers and parents in supporting students. The integration of credible, interactive, and empathetic messages was found to improve the effectiveness of early detection. This study contributes to the development of a humanistic and applicable digital intervention model and provides implications for future research in technology-based mental health.